Using MEMS in class D amplifiers for standard GSM carrier - Al-Khateeb, Khalid A. Saeed; M. Harun, Nik M. Yusri (2008)
The equivalent circuit of MEMS capacitive switches can be used to analyze a class D power amplifier, operated by a power supply of 3.7V. The system is intended for GSM audio frequency to produce an output power of (0.5-1.0) mW at a load output impedance of (8-10) Q. The system gain must be greater than 33 dBm and the estimated loss (0.5-1) dB. A model for the power amplifier using MEMS passive devices has been developed. The model helps to determine the design parameters that affect the performance and reliability of the system that operate an RF transceiver. The optimization of the amplifier and the MEMS capacitor switching devices and how to integrate the system, will also be discussed. The design and the equivalent circuit were simulated using a PSpice model.